Preparation process of high cycle stability sodium ion battery hard carbon-based negative electrode material

By utilizing a green preparation process for biomass materials, a hard carbon-based anode material for sodium-ion batteries with high cycle stability was prepared, overcoming the shortcomings of existing materials in terms of overall performance and improving the cycle performance and storage capacity of sodium-ion batteries.

CN121672472BActive Publication Date: 2026-11-06ZHEJIANG WESTON NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511738141.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-25
Publication Date
2026-11-06
Estimated Expiration
2045-11-25

AI Technical Summary

Technical Problem

Existing sodium-ion battery anode materials lack key characteristics in terms of practical value and commercial prospects, such as simple synthesis, low cost, and green and environmentally friendly synthesis routes, and lack electrode materials with excellent comprehensive performance.

Method used

A simple, feasible, green, and non-toxic preparation method using biomass materials is employed, including biomass composite preparation, sugarcane pretreatment, alkali lignin extraction, lignin purification, pre-carbonization, hydrothermal activation treatment, precursor preparation, and carbonization, to prepare a hard carbon-based anode material for sodium-ion batteries with high cycle stability.

Benefits of technology

It improves the cycle performance and sodium storage capacity of sodium-ion batteries, increases the specific surface area and interlayer spacing of materials, promotes the storage and transport of sodium ions, and improves the rate performance of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672472B_ABST
    Figure CN121672472B_ABST
Patent Text Reader

Abstract

This invention relates to a preparation process for a high-cycle-stability hard carbon-based anode material for sodium-ion batteries. The process includes: preparation of a biomass composite, pretreatment of sugarcane, extraction of alkali lignin, purification of lignin, pre-carbonization, precursor preparation, and carbonization steps. This invention creatively combines doping and hydrothermal activation-carbonization methods to synthesize three-dimensional hard carbon materials. The resulting material exhibits high cycle life and stable rate performance. The raw materials used in this invention are inexpensive and readily available, and the process is pollution-free, low-cost, and has a long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a preparation process for a hard carbon-based anode material for sodium-ion batteries with high cycle stability. Background Technology

[0002] The continuous development of modern society has led to an ever-increasing energy consumption. The ongoing exploitation and utilization of traditional fossil fuels continues to negatively impact the natural ecosystem and global climate. Developing new renewable and clean energy sources has become a key technological focus. Due to the intermittent nature of clean energy supply, exploring and researching large-scale energy storage devices capable of stably and reliably storing generated energy has become a crucial link in the efficient utilization of clean energy. Compared to common energy storage devices like lithium-ion batteries, sodium-ion batteries have become a strong candidate for new large-scale energy storage technology due to their wide and abundant resource distribution, low cost, and wide operating temperature range. Currently, the bottleneck in sodium-ion battery technology development lies in the lack of electrode materials with excellent comprehensive performance. Among various types of cathode materials, layered transition metal oxides, polyanionic materials, and Prussian blue compounds have been extensively studied and have undergone small-scale practical verification. Among anode materials, those with in-depth research value include carbon materials, titanium-based materials, and alloy materials. While the performance of some of these anode materials has been continuously improved thanks to researchers' efforts, they still lack some key characteristics in terms of practical value and commercial prospects, such as simple synthesis, low cost, and environmentally friendly synthesis routes. As a type of amorphous carbon, hard carbon materials are considered highly valuable anode materials due to their simple preparation process, low preparation cost, diverse raw material sources, tunable microstructure, and low electrochemical potential.

[0003] Against this backdrop, this patent utilizes biomass materials, which are widely available and inexpensive, to construct hard carbon materials through a simple, feasible, green, and non-toxic preparation method. Summary of the Invention

[0004] To address the above problems, this invention provides a preparation process for a high-cycle-stability hard carbon-based anode material for sodium-ion batteries.

[0005] This invention relates to a preparation process for a high-cycle-stability hard carbon-based anode material for sodium-ion batteries, comprising the following steps: preparation of biomass composite, pretreatment of sugarcane, extraction of alkali lignin, purification of lignin, pre-carbonization, hydrothermal activation treatment, preparation of precursor, and carbonization.

[0006] Preferably, step (1) involves the preparation of the biomass complex. Corn starch was dissolved in deionized water and preheated in a water bath with stirring. Then, saccharifying enzyme was added and stirred continuously to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, the mixture was centrifuged several times and then transferred to a drying oven for drying and dehydration. The dehydrated corn starch was then mixed with cellulose powder and placed in a ball mill jar lined with polytetrafluoroethylene for ball milling. Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder, sieve it to obtain sugarcane powder. Step (3) Alkali lignin extraction After the raw materials are mixed with sodium hydroxide solution, the mixture is heated and kept warm. After the reaction is complete, the mixture is filtered and separated using nylon cloth. The pulp residue is cleaned with deionized water until the filtrate is neutral. Acetic acid solution is added to the filtrate to adjust the pH and precipitate the lignin. Step (4) Lignin purification The separated lignin was further purified by the following method: weigh the lignin from step (3) and add H2SO4. Heat and stir in a water bath. After the reaction is complete, dilute with deionized water and treat at high temperature in an autoclave. After the reaction is complete, filter in a glass crucible and wash with deionized water until neutral. Dry at low temperature and grind for later use. Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), place them in a corundum boat, then pre-carbonize them in a muffle furnace, collect the powder, and ball-mill them in a ball mill. Place the pre-carbonized carbon in a mortar and grind it, then place the pre-carbonized carbon in a sodium hydroxide solution, seal the solution and heat it, then wash it alternately with water and ethanol and filter and dry it. Step (6) Precursor preparation Weigh the pre-carbonized powder and NaOH (analytical grade) separately. Mix them according to the ratio of unactivated, precursor and activator. Place them in a polytetrafluoroethylene reactor, add deionized water, and place them in a forced-air drying oven to react. After cooling to room temperature, remove them for later use. Connect the Buchner funnel and the vacuum filtration flask. Place clean filter paper in the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water dropwise, pour it into the funnel, and then filter it using a vacuum pump. Dry the mixture to obtain the precursor. Step (7) Carbonization Sodium dihydrogen phosphate (NaH2PO4) and the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace and calcined. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0007] Preferably, step (1) involves the preparation of the biomass complex. Dissolve 30-50g of corn starch in 120-150mL of deionized water and preheat in a water bath at 50-70℃ for 10-20 minutes. Then add 320-400mg of saccharifying enzyme with an activity of 100,000-150,000 and continue stirring for 3-6 hours to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and then transfer to a drying oven at 50-60℃ for 10-12 hours for dehydration. Mix the dehydrated corn starch with cellulose powder and place it in a ball mill jar lined with polytetrafluoroethylene. Ball mill thoroughly at 400-500rpm for 4-6 hours.

[0008] The advantage of using this invention is that the mutual doping of corn starch and cellulose powder results in a large interlayer spacing and disorder in the composite-derived hard carbon. At the same carbonization temperature, the composite-derived hard carbon has the largest C=O ratio, which is beneficial for the storage and rapid transport of sodium ions.

[0009] Preferably, step (2) involves pretreatment of the sugarcane. Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through an 80-100 mesh sieve to obtain sugarcane powder.

[0010] As a preferred option, step (3) involves alkali lignin extraction. Cotton stalks are mixed with 20-30% sodium hydroxide solution in a ratio of 1:1 to 1:10 and heated in a rotary cooker at 120-160℃ for 1-2 hours. After the reaction is complete, the mixture is filtered and separated using nylon cloth. The pulp residue is cleaned with deionized water until the filtrate is neutral. Acetic acid solution is added to the filtrate to adjust the pH to 3-4, thereby precipitating the lignin.

[0011] As a preferred option, step (4) involves lignin purification. The separated lignin is further purified by the following method: Weigh 1-3g of lignin from step (3) and add 10-20mL of 50-80% H2SO4. Stir in a water bath for 1-3 hours at a temperature of 30-40℃. After the reaction is complete, add deionized water to dilute to 5-8%. Treat in an autoclave at high temperature for 1-2 hours. After the reaction is complete, filter in a glass crucible and wash with deionized water until neutral. Dry at a low temperature of 50-60℃ and grind for later use.

[0012] Preferably, step (5) involves pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), take 1-2g and place it in a corundum boat. Then, place it in a muffle furnace and pre-carbonize it at 200-300℃ for 6-8h. After that, collect the powder and ball mill it at a speed of 1000-1500rad / min for 10-15min. Place the pre-carbonized carbon in a mortar and grind it for 1-2h. Then, place the pre-carbonized carbon in a 1-3wt% sodium hydroxide solution, seal the solution and heat it to 100-150℃ for more than 20-24h. Then, wash it alternately with water and ethanol and filter and dry it.

[0013] Preferably, step (6) involves precursor preparation. Weigh 1-3g of the pre-carbonized powder and 1-3g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator of 1:1-1:5. Place the mixture in a 100-150mL PTFE reactor, add 30-40mL of deionized water, and place it in a forced-air drying oven. React at 150-200℃ for 15-20h. Cool to room temperature and remove for later use. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper in the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 6-7, and then dry in an oven to obtain the precursor.

[0014] The advantage of using this invention is that the NaOH-activated precursor can corrode carbon materials, causing them to break down and increasing their specific surface area, thus providing more active sites for sodium ion storage. However, the concentration of the activator should not be too high, otherwise it will cause severe collapse of the carbon material structure, which is not conducive to the transport of sodium ions.

[0015] The advantage of using this invention is that NaOH reacts with the aromatic rings of carbon materials under high temperature and high pressure to produce the above-mentioned series of reactions. The C atoms involved in the reaction generate gas that escapes, causing defects and micropores on the surface of some graphite domains of carbon materials, thus providing active sites for sodium storage.

[0016] Preferably, step (7) carbonization 0.2-0.5g of sodium dihydrogen phosphate (NaH2PO4) and 80-120mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 700-1500℃ with a heating rate of 5-10℃ / min for 1-2h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0017] The advantage of using this invention is that, as the carbonization temperature increases, the dehydration and decarboxylation reactions of carbon, hydrogen, oxygen and nitrogen atoms in the raw materials gradually proceed, resulting in the disappearance of a large number of polar functional groups, the polarity and hydrophilicity of the sample gradually weaken, and it gradually becomes aromatic.

[0018] The advantages of using this invention are that, as the temperature increases, the pores of the sample become more developed, with macropores and mesopores nested together. This is due to the gradual increase in carbonization temperature and the continuous overflow of gas. The loose and porous structure is conducive to the insertion and extraction of sodium ions, and the electrolyte can enter the electrode material more easily, thereby shortening the diffusion distance between sodium ions and electrons and thus improving the rate performance of sodium-ion batteries.

[0019] The advantage of this invention is that, due to the larger atomic radius of phosphorus compared to carbon atoms, the PC bond length is longer than the C-C bond length, forming an arched three-dimensional structure. This effectively modifies the structure of hard carbon materials, thus expanding the interlayer spacing in hard carbon (HC). This expansion allows for more Na... + It is contained in the interlayer pores, resulting in increased sodium storage capacity and improved cycling performance.

[0020] In summary, the present invention has the following beneficial effects: 1. The advantage of using this invention is that the mutual doping of corn starch and cellulose powder results in the composite-derived hard carbon having a large interlayer spacing and a high degree of disorder. At the same carbonization temperature, the composite-derived hard carbon has the largest C=O ratio, which is beneficial for the storage and rapid transport of sodium ions. 2. The advantage of using this invention is that the NaOH-activated precursor can corrode carbon materials, causing them to break up and increasing their specific surface area, thus providing more active sites for the storage of sodium ions. However, the concentration of the activator should not be too high, otherwise it will cause severe collapse of the carbon material structure, which is not conducive to the transport of sodium ions. 3. The advantage of using this invention is that NaOH and the aromatic ring of carbon material undergo the above-mentioned series of reactions under high temperature and high pressure. The C atoms participating in the reaction generate gas that overflows, causing defects and micropores on the surface of some carbon material graphite domains, providing sodium storage active sites. 4. The advantage of using this invention is that, as the carbonization temperature increases, the dehydration and decarboxylation reactions of carbon, hydrogen, oxygen and nitrogen atoms in the raw materials gradually proceed, resulting in the disappearance of a large number of polar functional groups, the polarity and hydrophilicity of the sample gradually weaken, and it gradually becomes aromatic. 5. The advantage of using this invention is that as the temperature increases, the pores of the sample become more developed, with macropores and mesopores nested together. This is due to the gradual increase in carbonization temperature and the continuous overflow of gas. The loose and porous structure is conducive to the insertion and extraction of sodium ions, and the electrolyte can enter the electrode material more easily, thereby shortening the diffusion distance between sodium ions and electrons, and thus improving the rate performance of sodium-ion batteries. 6. The advantage of this invention is that, because phosphorus has a larger atomic radius than carbon atoms, the PC bond length is longer than the C-C bond length, forming an arched three-dimensional structure, which effectively modifies the structure of hard carbon materials, thus expanding the interlayer spacing in hard carbon (HC). This expansion allows for more Na... + It is contained in the interlayer pores, resulting in increased sodium storage capacity and improved cycling performance. Attached Figure Description

[0021] Figure 1 This is a process flow diagram of the preparation process of a high cycle stability sodium-ion battery hard carbon-based anode material according to the present invention; Figure 2 This is an electron microscope image of the biomass-derived hard carbon anode material prepared in Example 4 of this invention; Figure 3 This is another electron microscope image of the biomass-derived hard carbon anode material prepared in Example 4 of the present invention. Detailed Implementation

[0022] The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the invention. Any modifications or substitutions made to the methods, steps, or conditions of the present invention without departing from the spirit and essence of the invention are within the scope of the invention.

[0023] Unless otherwise specified, the techniques used in the embodiments are conventional methods well known to those skilled in the art. Furthermore, all component raw materials used in the embodiments are known commercially available products.

[0024] Example 1

[0025] Step (1) Preparation of biomass complex Dissolve 30g of corn starch in 120mL of deionized water and preheat in a 50℃ water bath for 10min. Then add 320mg of 100,000 activity saccharifying enzyme and stir continuously for 3h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 50℃ for 10h for dehydration. Mix the dehydrated corn starch with cellulose powder and place in a polytetrafluoroethylene-lined ball mill jar. Ball mill thoroughly at 400rpm for 4h.

[0026] Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through an 80-mesh sieve to obtain sugarcane powder.

[0027] Step (3) Alkali lignin extraction Cotton stalks were mixed with 20% sodium hydroxide solution in a 1:1 ratio and heated in a rotary cooker at 120°C for 1 hour. After the reaction was completed, the mixture was filtered and separated using nylon cloth. The pulp residue was cleaned with deionized water until the filtrate was neutral. Acetic acid solution was added to the filtrate to adjust the pH to 3, and lignin was precipitated.

[0028] Step (4) Lignin purification The separated lignin was further purified by the following method: 1g of lignin from step (3) was weighed and added to 10mL of 50% H2SO4. The mixture was stirred in a water bath for 1 hour at 30℃. After the reaction was completed, deionized water was added to dilute it to 5%. The mixture was then subjected to high-temperature treatment in an autoclave for 1 hour. After the reaction was completed, the mixture was filtered through a glass crucible and washed with deionized water until neutral. After drying at 50℃, it was ground for later use.

[0029] Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), 1g was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 200°C for 6 hours. The powder was then collected and ball-milled at 1000 rad / min for 10 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 1 hour. The pre-carbonized carbon was then placed in a 1 wt% sodium hydroxide solution, the solution was sealed and heated to 100°C for more than 20 hours, and then washed alternately with water and ethanol and filtered and dried.

[0030] Step (6) Precursor preparation Weigh 1g of pre-carbonized powder and 1g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:1). Place the mixture in a 100mL polytetrafluoroethylene reactor, add 30mL of deionized water, and place it in a forced-air drying oven. React at 150℃ for 15h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 6, then dry in an oven to obtain the precursor.

[0031] Step (7) Carbonization 0.2g sodium dihydrogen phosphate (NaH2PO4) and 80mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 700℃ with a heating rate of 5℃ / min for 1h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0032] Example 2

[0033] Step (1) Preparation of biomass complex Dissolve 35g of corn starch in 130mL of deionized water and preheat in a 55℃ water bath for 14min. Then add 360mg of 110,000 activity saccharifying enzyme and stir continuously for 4h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 52℃ for 10h for dehydration. Mix the dehydrated corn starch with cellulose powder and place it in a polytetrafluoroethylene-lined ball mill jar. Ball mill thoroughly at 420rpm for 4h.

[0034] Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through an 80-mesh sieve to obtain sugarcane powder.

[0035] Step (3) Alkali lignin extraction Cotton stalks were mixed with 20% sodium hydroxide solution at a ratio of 1:4 and heated in a rotary cooker at 130°C for 1 hour. After the reaction was completed, the mixture was filtered and separated using nylon cloth. The pulp residue was cleaned with deionized water until the filtrate was neutral. Acetic acid solution was added to the filtrate to adjust the pH to 3, which precipitated the lignin.

[0036] Step (4) Lignin purification The separated lignin was further purified by the following method: Weigh 1-3g of lignin from step (3) and add 12mL of 60% H2SO4. Stir in a water bath for 1 hour at 32℃. After the reaction, add deionized water to dilute to 6% and treat at high temperature in an autoclave for 1 hour. After the reaction, filter in a glass crucible and wash with deionized water until neutral. Dry at 52℃ and grind for later use.

[0037] Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), 1g was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 230°C for 6 hours. The powder was then collected and ball-milled at 1200 rad / min for 12 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 1 hour. The pre-carbonized carbon was then placed in a 1 wt% sodium hydroxide solution, the solution was sealed and heated to 120°C for more than 22 hours, and then washed alternately with water and ethanol and filtered and dried.

[0038] Step (6) Precursor preparation Weigh 1g of the pre-carbonized powder and 1g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:2). Place the mixture in a 120mL PTFE reactor, add 32mL of deionized water, and place it in a forced-air drying oven. React at 170℃ for 17h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 6, then dry in an oven to obtain the precursor.

[0039] Step (7) Carbonization 0.3g sodium dihydrogen phosphate (NaH2PO4) and 90mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 1000℃ with a heating rate of 6℃ / min for 1h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0040] Example 3

[0041] Step (1) Preparation of biomass complex Dissolve 40g of corn starch in 140mL of deionized water and preheat in a 60℃ water bath for 14min. Then add 360mg of saccharifying enzyme with an activity of 130,000 and continue stirring for 5h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 55℃ for 11h for dehydration. Mix the dehydrated corn starch with cellulose powder and place it in a ball mill jar lined with polytetrafluoroethylene. Ball mill at 450rpm for 5h.

[0042] Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through a 100-mesh sieve to obtain sugarcane powder.

[0043] Step (3) Alkali lignin extraction Cotton stalks were mixed with 25% sodium hydroxide solution at a ratio of 1:8 and heated in a rotary cooker at 140°C for 2 hours. After the reaction was completed, the mixture was filtered and separated using nylon cloth. The pulp residue was cleaned with deionized water until the filtrate was neutral. Acetic acid solution was added to the filtrate to adjust the pH to 4, which precipitated the lignin.

[0044] Step (4) Lignin purification The separated lignin was further purified by the following method: Weigh 1-3g of lignin from step (3) and add 15mL of 70% H2SO4. Stir in a water bath for 2 hours at 35℃. After the reaction, add deionized water to dilute to 6% and treat at high temperature in an autoclave for 1 hour. After the reaction, filter in a glass crucible and wash with deionized water until neutral. Dry at 56℃ and grind for later use.

[0045] Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), 2g was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 260°C for 7 hours. The powder was then collected and ball-milled at 1300 rad / min for 15 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 2 hours. The pre-carbonized carbon was then placed in a 2wt% sodium hydroxide solution, the solution was sealed and heated to 130°C for more than 22 hours, and then washed alternately with water and ethanol and filtered and dried.

[0046] Step (6) Precursor preparation Weigh 2g of the pre-carbonized powder and 2g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:3). Place the mixture in a 130mL PTFE reactor, add 36mL of deionized water, and place it in a forced-air drying oven. React at 170℃ for 18h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 7, then dry in an oven to obtain the precursor.

[0047] Step (7) Carbonization 0.4 g of sodium dihydrogen phosphate (NaH2PO4) and 100 mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 1200 °C with a heating rate of 8 °C / min for 2 h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0048] Example 4

[0049] Step (1) Preparation of biomass complex Dissolve 50g of corn starch in 150mL of deionized water and preheat in a 70℃ water bath for 20min. Then add 400mg of 150,000 activity saccharifying enzyme and stir continuously for 6h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 60℃ for 12h for dehydration. Mix the dehydrated corn starch with cellulose powder and place it in a polytetrafluoroethylene-lined ball mill jar. Ball mill thoroughly at 500rpm for 6h.

[0050] Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through a 100-mesh sieve to obtain sugarcane powder.

[0051] Step (3) Alkali lignin extraction Cotton stalks were mixed with 30% sodium hydroxide solution at a ratio of 1:10 and heated in a rotary cooker at 160°C for 2 hours. After the reaction was completed, the mixture was filtered and separated using nylon cloth. The pulp residue was cleaned with deionized water until the filtrate was neutral. Acetic acid solution was added to the filtrate to adjust the pH to 4, and lignin was precipitated.

[0052] Step (4) Lignin purification The separated lignin was further purified by the following method: Weigh 3g of lignin from step (3) and add 20mL of 80% H2SO4. Stir in a water bath for 3 hours at 40℃. After the reaction, add deionized water to dilute to 8% and treat at high temperature in an autoclave for 2 hours. After the reaction, filter in a glass crucible and wash with deionized water until neutral. Dry at 60℃ and grind for later use.

[0053] Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), 2g of the mixture was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 300°C for 8 hours. The powder was then collected and ball-milled at 1500 rad / min for 15 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 2 hours. The pre-carbonized carbon was then placed in a 3wt% sodium hydroxide solution, the solution was sealed and heated to 150°C for more than 24 hours, and then washed alternately with water and ethanol and filtered and dried.

[0054] Step (6) Precursor preparation Weigh 3g of the pre-carbonized powder and 3g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:5). Place the mixture in a 150mL polytetrafluoroethylene reactor, add 40mL of deionized water, and place it in a forced-air drying oven. React at 200℃ for 20h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 7, then dry in an oven to obtain the precursor.

[0055] Step (7) Carbonization 0.5 g of sodium dihydrogen phosphate (NaH2PO4) and 120 mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 1500 °C with a heating rate of 10 °C / min for 2 h. The resulting samples were then ground to obtain phosphorus-doped biomass-derived hard carbon material. Electron micrographs of the obtained materials are shown below. Figure 2 (Magnified 1000 times) and Figure 3 (Magnified 2000 times).

[0056] Comparative Example 1

[0057] Step (1) Preparation of biomass complex Dissolve 30g of corn starch in 120mL of deionized water and preheat in a 50℃ water bath for 10min. Then add 320mg of 100,000 activity saccharifying enzyme and stir continuously for 3h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 50℃ for 10h for dehydration. Mix the dehydrated corn starch with cellulose powder and place in a polytetrafluoroethylene-lined ball mill jar. Ball mill thoroughly at 400rpm for 4h.

[0058] Step (2) Alkali lignin extraction Cotton stalks were mixed with 20% sodium hydroxide solution in a 1:1 ratio and heated in a rotary cooker at 120°C for 1 hour. After the reaction was completed, the mixture was filtered and separated using nylon cloth. The pulp residue was cleaned with deionized water until the filtrate was neutral. Acetic acid solution was added to the filtrate to adjust the pH to 3, and lignin was precipitated.

[0059] Step (3) Lignin purification The separated lignin was further purified by the following method: 1g of lignin from step (3) was weighed and added to 10mL of 50% H2SO4. The mixture was stirred in a water bath for 1 hour at 30℃. After the reaction was completed, deionized water was added to dilute it to 5%. The mixture was then subjected to high-temperature treatment in an autoclave for 1 hour. After the reaction was completed, the mixture was filtered through a glass crucible and washed with deionized water until neutral. After drying at 50℃, it was ground for later use.

[0060] Step (4) Pre-carbonization: After mixing the samples obtained in steps (1) and (3), 1g was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 200°C for 6 hours. The powder was then collected and ball-milled at 1000 rad / min for 10 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 1 hour. The pre-carbonized carbon was then placed in a 1 wt% sodium hydroxide solution, the solution was sealed and heated to 100°C for more than 20 hours, and then washed alternately with water and ethanol and filtered and dried.

[0061] Step (5) Precursor preparation Weigh 1g of pre-carbonized powder and 1g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:1). Place the mixture in a 100mL polytetrafluoroethylene reactor, add 30mL of deionized water, and place it in a forced-air drying oven. React at 150℃ for 15h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 6, then dry in an oven to obtain the precursor.

[0062] Step (6) Carbonization 0.2g sodium dihydrogen phosphate (NaH2PO4) and 80mg of the carbon precursor obtained in step (5) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 700℃ with a heating rate of 5℃ / min for 1h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0063] Comparative Example 2

[0064] Step (1) Preparation of biomass complex Dissolve 30g of corn starch in 120mL of deionized water and preheat in a 50℃ water bath for 10min. Then add 320mg of 100,000 activity saccharifying enzyme and stir continuously for 3h to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and transfer to a drying oven to dry at 50℃ for 10h for dehydration. Mix the dehydrated corn starch with cellulose powder and place in a polytetrafluoroethylene-lined ball mill jar. Ball mill thoroughly at 400rpm for 4h.

[0065] Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through an 80-mesh sieve to obtain sugarcane powder.

[0066] Step (3) Pre-carbonization: After mixing the samples obtained in steps (1) and (2), 1g was placed in a corundum boat and then placed in a muffle furnace for pre-carbonization at 200°C for 6 hours. The powder was then collected and ball-milled at 1000 rad / min for 10 minutes. The pre-carbonized carbon was then placed in a mortar and ground for 1 hour. The pre-carbonized carbon was then placed in a 1wt% sodium hydroxide solution, the solution was sealed and heated to 100°C for more than 20 hours, and then washed alternately with water and ethanol and filtered and dried.

[0067] Step (4) Precursor preparation Weigh 1g of pre-carbonized powder and 1g of NaOH (analytical grade). Mix them according to the ratio of unactivated precursor to activator (mass ratio 1:1). Place the mixture in a 100mL polytetrafluoroethylene reactor, add 30mL of deionized water, and place it in a forced-air drying oven. React at 150℃ for 15h, then cool to room temperature and set aside. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper inside the funnel. Place the mixture of precursor and NaOH after hydrothermal treatment in a beaker, add dilute nitric acid and deionized water, pour into the funnel, and then filter using a vacuum pump. Repeat the operation until the pH reaches 6, then dry in an oven to obtain the precursor.

[0068] Step (5) Carbonization 0.2g sodium dihydrogen phosphate (NaH2PO4) and 80mg of the carbon precursor obtained in step (4) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 700℃ with a heating rate of 5℃ / min for 1h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

[0069] Comparison of detection experiments: The hard carbon anode materials obtained in Examples 1 to 4 and comparative products 1 and 2 were tested using the following specific testing methods: Constant current charge-discharge test (GCD) This patent conducts cycle performance tests on the battery at current densities of 30 and 300 mA / g, respectively. Gradient current cycle testing refers to subjecting the battery to a certain number of cycles at different current densities to examine its rate performance. This patent conducts rate performance tests on the battery at current densities of 30-1200 and 30-1500 mA / g, respectively. The above tests were performed on a LAND CT2001A tester, with a test voltage window of 0.001-3 V.

[0070] Electrochemical impedance spectroscopy (EIS) This patent uses the Shanghai Chenhua CHI660E to plot AC impedance spectra, with a test frequency range of 0.01-100 kHz.

[0071] Table 1 Constant Current Charge-Discharge Cycling Method

[0072] Table 1 shows that Example 4 is the best, while the comparative example is relatively poor. The plateau in cycle performance and coulombic efficiency is due to the fact that at lower calcination temperatures, the samples have excessively large interlayer spacing, allowing sodium ions to freely enter and exit the carbon layers with fewer intercalation reactions. Simultaneously, their high degree of disorder indicates a large number of internal defect structures, providing numerous active sites for sodium ion adsorption. Increasing temperature leads to a decrease in defect content, while the pseudo-graphite microcrystalline structure within the material develops, increasing sodium ion insertion and extraction. Furthermore, the specific surface area increases significantly with increasing NaOH activation concentration, providing a large number of active sites for sodium storage. Micropores improve the specific surface area and sodium storage capacity of the carbon material, while mesopores facilitate electrolyte wetting and sodium ion transport.

[0073] As the temperature rises, the pores of the sample become more developed, with macropores and mesopores nested together. This is due to the gradual increase in carbonization temperature and the continuous overflow of gas. The loose and porous structure is conducive to the insertion and extraction of sodium ions, and the electrolyte can enter the electrode material more easily, thereby shortening the diffusion distance between sodium ions and electrons and thus improving the rate performance of sodium-ion batteries.

[0074] Table 2 Electrochemical Impedance Spectroscopy (EIS)

[0075] Table 2 shows that Example 4 is the best, while the comparative example is worse. This indicates that during the sodium storage process... It has good conductivity and ion transport capabilities, thus exhibiting excellent cycling and rate performance.

[0076] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A preparation process for a high-cycle-stability hard carbon-based anode material for sodium-ion batteries, characterized in that, include: Step (1) Preparation of biomass complex Corn starch was dissolved in deionized water and preheated in a water bath with stirring. Then, saccharifying enzyme was added and stirred continuously to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, the mixture was centrifuged several times and then transferred to a drying oven for drying and dehydration. The dehydrated corn starch was then mixed with cellulose powder and placed in a ball mill jar lined with polytetrafluoroethylene for ball milling. Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder, sieve it to obtain sugarcane powder. Step (3) Alkali lignin extraction After mixing cotton stalks with sodium hydroxide solution, the mixture is heated and kept warm. After the reaction is complete, the mixture is filtered and separated using nylon cloth. The pulp residue is cleaned with deionized water until the filtrate is neutral. Acetic acid solution is added to the filtrate to adjust the pH and precipitate the lignin. Step (4) Lignin purification The separated lignin was further purified by the following method: weigh the lignin from step (3) and add H2SO4. Heat and stir in a water bath. After the reaction is complete, dilute with deionized water and treat at high temperature in an autoclave. After the reaction is complete, filter in a glass crucible and wash with deionized water until neutral. Dry at low temperature and grind for later use. Step (5) Pre-carbonization: After mixing the samples obtained in steps (1), (2), and (5), take 1-2g and place it in a corundum boat. Then, place it in a muffle furnace and pre-carbonize it at 200-300℃ for 6-8h. After that, collect the powder and ball mill it at 1000-1500rad / min for 10-15min. Place the pre-carbonized carbon in a mortar and grind it for 1-2h. Then, place the pre-carbonized carbon in a 1-3wt% sodium hydroxide solution, seal the solution and heat it to 100-150℃ for more than 20-24h. Then, wash it alternately with water and ethanol and filter and dry it. Step (6) Precursor preparation Weigh the pre-carbonized powder obtained in step (5), and weigh the analytical grade NaOH separately. Mix the pre-carbonized powder obtained in step (5) with the analytical grade NaOH, place it in a polytetrafluoroethylene reaction vessel, add deionized water, place it in a forced-air drying oven to react, and remove it for use after cooling to room temperature. Connect the Buchner funnel and the vacuum filtration flask, place clean filter paper in the funnel, place the mixture of the pre-carbonized powder obtained in step (5) after hydrothermal treatment and the analytical grade NaOH in a beaker, add dilute nitric acid and deionized water, pour it into the funnel, filter it using a vacuum pump, dry it, and obtain the precursor. Step (7) Carbonization 0.2-0.5g of sodium dihydrogen phosphate (NaH2PO4) and 80-120mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace and calcined. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

2. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 1, characterized in that: Step (1) Preparation of biomass complex Dissolve 30-50g of corn starch in 120-150mL of deionized water and preheat in a water bath at 50-70℃ for 10-20 minutes. Then add 320-400mg of saccharifying enzyme with an activity of 100,000-150,000 and continue stirring for 3-6 hours to allow the saccharifying enzyme to fully react with the corn starch. After complete enzymatic hydrolysis, centrifuge several times and then transfer to a drying oven at 50-60℃ for 10-12 hours for dehydration. Mix the dehydrated corn starch with cellulose powder and place it in a ball mill jar lined with polytetrafluoroethylene. Ball mill thoroughly at 400-500rpm for 4-6 hours.

3. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 2, characterized in that: Step (2) Sugarcane pretreatment Wash the sugarcane repeatedly with deionized water until the ash and impurities on the surface are removed; dry the washed sugarcane to remove water, then crush it into powder and pass it through an 80-100 mesh sieve to obtain sugarcane powder.

4. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 3, characterized in that: Step (3) Alkali lignin extraction Cotton stalks are mixed with 20-30% sodium hydroxide solution in a ratio of 1:1 to 1:10 and heated in a rotary cooker at 120-160℃ for 1-2 hours. After the reaction is complete, the mixture is filtered and separated using nylon cloth. The pulp residue is cleaned with deionized water until the filtrate is neutral. Acetic acid solution is added to the filtrate to adjust the pH to 3-4, thereby precipitating the lignin.

5. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 4, characterized in that: Step (4) Lignin purification The separated lignin is further purified by the following method: Weigh 1-3g of lignin from step (3) and add 10-20mL of 50-80% H2SO4. Stir in a water bath for 1-3 hours at a temperature of 30-40℃. After the reaction is complete, add deionized water to dilute to 5-8%. Treat in an autoclave at high temperature for 1-2 hours. After the reaction is complete, filter in a glass crucible and wash with deionized water until neutral. Dry at a low temperature of 50-60℃ and grind for later use.

6. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 5, characterized in that: Step (6) Precursor preparation Weigh 1-3g of the pre-carbonized powder obtained in step (5), and weigh 1-3g of analytical grade NaOH. Mix the pre-carbonized powder obtained in step (5) with analytical grade NaOH in a mass ratio of 1:1-1:

5. Place the mixture in a 100-150mL polytetrafluoroethylene reactor, add 30-40mL of deionized water, place it in a forced-air drying oven, and react at 150-200℃ for 15-20h. Cool it to room temperature and remove it for later use. Connect the Buchner funnel and the vacuum filtration flask, and place clean filter paper in the funnel. Place the mixture of the pre-carbonized powder obtained in step (5) after hydrothermal treatment and analytical grade NaOH in a beaker, add dilute nitric acid and deionized water, pour it into the funnel, and then use a vacuum pump to filter it. Repeat the operation until the pH is 6-7, and then place it in an oven to dry to obtain the precursor.

7. The preparation process of a high-cycle-stability sodium-ion battery hard carbon-based anode material according to claim 6, characterized in that: Step (7) Carbonization 0.2-0.5g of sodium dihydrogen phosphate (NaH2PO4) and 80-120mg of the carbon precursor obtained in step (6) were placed on the upstream and downstream sides of a tube furnace, respectively, and calcined at 700-1500℃ with a heating rate of 5-10℃ / min for 1-2h. The resulting sample was then ground to obtain phosphorus-doped biomass-derived hard carbon material.

Citation Information

Patent Citations

  • Hard carbon material, preparation method thereof and sodium ion battery

    CN116514105A

  • Method for rapidly preparing hard carbon negative electrode material, obtained product and sodium ion battery

    CN118771351A